Pengaruh Ukuran Perusahaan, Leverage, Dan Likuidtas Terhadap Kinerja Keuangan - Adinda Nilawati; Ai Hendrani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Financial performance describes how well a company's financial performance is when it meets its objectives and utilizes its resources well in using assets to generate and collect profits. The purpose of this study was to determine the effect of firm size, leverage, and liquidity on the financial performance of insurance that has gone public in Indonesia from 2016 to 2022. This research model uses a causality design and uses panel data regression analysis with secondary data. Eviews 12 software is used to measure the data. The sample was selected using a purposive sampling approach and included 56 insurance financial statement data of 18 companies from 2016 to 2022. Based on the findings, financial performance is simultaneously influenced by firm size, leverage, and liquidity. Firm size and leverage partially have no impact on financial performance, while liquidity partially has an impact on financial performance.